DEIXIS IN THE CLEVER SERVANT STORY - Liawati, Azizah; Rizkiani, Siska; Jamaludin, Agil (PROJECT (Professional Journal of English Education), 2020)
Pragmatics is a study of contextual meaning. Finding out the context and meaning of a conversation can be learned through deixis. This research analyzes types of deixis such as personal, time and place deixis. This research discusing about recount text entitled "The Clever Servant" as the instrument of this study. This research applied a descriptive qualitative method. The steps to analyze data are searching the story, reading the story, finding the data based on three kinds of deixis above. In this research, there was 27 deixis found in the text. The most common type of deixis is person deixis with 19 words. Whereas place deixis has 5 words and time deixis has 3 words. In this study, the researcher find out that personal deixis is the dominant type in the text. Keywords:  Deixis, Pragmatics, The Clever Servant